RESEARCH ON THE INFLUENCE RELATIONSHIP BETWEEN CORPORATE RELATIONSHIP CAPITAL AND KNOWLEDGE TRANSFER EFFECT - Lin, Guangbo; Wang, Tienan (วารสารปัญญาภิวัฒน์, 2019)
In the context of a globalized economy, knowledge transfer between companies is one way to remain competitive. At present, most of the existing researches are from the internal technological development and knowledge transfer process of enterprises to inquire into the factors affecting the company’s knowledge transfer (Bao, 2014). Less is the research on the effect of knowledge transfer between organizations from the perspective of the relationship between the capital owned by the company itself and the emotional willingness factor it embeds in the behavioral impact. Based on this, this paper proposes and explores the following questions: whether the relationship capital owned by the company itself and the emotional willingness factors it brings embeds the corporate behavior and then affects the effect of knowledge transfer between organizations. Specifically, this paper explores the influence of corporate relationship capital on knowledge transfer effectiveness through the willingness of knowledge transfer. This paper starts from the four dimensions of corporate relationship capital (trust, commitment, conflict management, and effective communication) and examines their effects on knowledge transfer through knowledge transfer willingness. The results show that the willingness to transfer knowledge has some mediating effects in the influence of the two dimensions of trust and commitment on the effect of knowledge transfer. In the influence of conflict management and effective communication of corporate relationship capital on the effect of knowledge transfer, the willingness to transfer knowledge plays a completely mediating role.